2007
DOI: 10.5194/acp-7-2313-2007
|View full text |Cite
|
Sign up to set email alerts
|

Secondary aerosol formation from atmospheric reactions of aliphatic amines

Abstract: Abstract. Although aliphatic amines have been detected in both urban and rural atmospheric aerosols, little is known about the chemistry leading to particle formation or the potential aerosol yields from reactions of gas-phase amines. We present here the first systematic study of aerosol formation from the atmospheric reactions of amines. Based on laboratory chamber experiments and theoretical calculations, we evaluate aerosol formation from reaction of OH, ozone, and nitric acid with trimethylamine, methylami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
265
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(278 citation statements)
references
References 46 publications
10
265
0
3
Order By: Relevance
“…They can also undergo photooxidation and oxidation reactions with OH radicals, NO 3 radicals and O 3 in the ambient atmosphere to form non-volatile aerosol components. [13,[18][19][20] De Haan et al [21,22] observed that reactions between glyoxal and amines or amino acids can produce light-absorbing, nitrogen-containing imidazoles and oligomers. Particle phase amines have been extensively observed in many areas [9,17,[23][24][25] especially in ultrafine particles during nucleation [26][27][28] and particle growth [29] events.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They can also undergo photooxidation and oxidation reactions with OH radicals, NO 3 radicals and O 3 in the ambient atmosphere to form non-volatile aerosol components. [13,[18][19][20] De Haan et al [21,22] observed that reactions between glyoxal and amines or amino acids can produce light-absorbing, nitrogen-containing imidazoles and oligomers. Particle phase amines have been extensively observed in many areas [9,17,[23][24][25] especially in ultrafine particles during nucleation [26][27][28] and particle growth [29] events.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high vapour pressures of low-molecular-weight amines, over 150 gaseous amines [5,6] have been identified in the atmosphere from both natural and anthropogenic sources including animal husbandry, waste incineration and sewage treatment, marine sources and vehicle exhaust. [7][8][9][10][11][12] Gaseous amine concentrations are usually at least an order of magnitude lower than that of ammonia in the atmosphere, [13] but they can reach as high as 23 % of that of ammonia in animal husbandry environments. [14] The mass concentration of gaseous amines varies from 0.3-4.2 ng m À3 in the marine atmosphere [15] to 70.4-561.4 mg m À3 near a commercial dairy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds could be amines of which a huge variety has been identified in the atmosphere 7 . Amines have already been predicted as likely candidates enhancing the nucleation rates based on quantum-chemical studies 8,9 and it has been observed that they contribute in the formation of secondary aerosol 10,11 . Laboratory studies as well as atmospheric measurements have also revealed that amines enhance ternary nucleation [12][13][14] .…”
Section: Ternary H 2 So 4 -H 2 O-dimethylamine Nucleationmentioning
confidence: 99%
“…The importance of amines for NPF has recently been established by field (Angelino et al, 2001;Makela et al, 2001;Smith et al, 2010;Zhao et al, 2011) and laboratory experiments (Murphy et al, 2007;Berndt et al, 2010;Erupe et al, 2011;Bzdek et al, 2010;Zhao et al, 2011;Yu et al, 2012;Zollner et al, 2012;Almeida et al, 2013;Jen et al, 2014;Kurten et al, 2014), as well as from modelling studies (Kurten et al, 2008;Barsanti et al, 2009;Bzdek et al, 2010;Ortega et al, 2012;Loukonen et al, 2010;Nadykto et al, 2011;Paasonen et al, 2012;Almeida et al, 2013;DePalma et al, 2014). On a molecular level, Kurten et al (2014) observed how DMA stabilises SA, increasing the stable cluster concentration by up to 6 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%